2015
DOI: 10.1039/c4gc02088j
|View full text |Cite
|
Sign up to set email alerts
|

A green chemistry-based classification model for the synthesis of silver nanoparticles

Abstract: The Multiple Criteria Decision Aiding (MCDA) method allows the derivation of a model that can be used for classification of existing or new production processes for silver nanoparticles in preference-ordered classes on the basis of the principles of green chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 103 publications
(203 reference statements)
1
57
0
Order By: Relevance
“…The use of environmentally friendly materials, in particular plant extracts, fungi, bacteria and enzymes, for the synthesis of MNPs showed numerous benefits in pharmaceutical and other biomedical applications . Green synthesis resulted also in being very cost effective and therefore can be used as a cheep suitable alternative for large‐scale production of MNPs.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The use of environmentally friendly materials, in particular plant extracts, fungi, bacteria and enzymes, for the synthesis of MNPs showed numerous benefits in pharmaceutical and other biomedical applications . Green synthesis resulted also in being very cost effective and therefore can be used as a cheep suitable alternative for large‐scale production of MNPs.…”
Section: Introductionsupporting
confidence: 86%
“…Several approaches have been reported in the literature using extracts from a variety of different plant species in combination with a variety of acids and metal salts. For example aqueous extracts of Ferocactus echidne have been used to reduce silver nitrate (AgNO 3 ) to form silver nanoparticles (AgNPs) within 6 h. It has been reported that both polyphenols and ascorbic acid present in aqueous Ferocactus echidne extracts can easily reduce silver ions and can also act as capping agents to prevent the agglomeration of AgNPs . Recently, gold nanoparticles (AuNPs) have been synthesized within 30 min by reducing sodium tetrachloroaurate (NaAuCl 4 ) with extracts of Darjeeling tea leaves.…”
Section: Introductionmentioning
confidence: 85%
“…Table 7 shows some of the rules extracted using the back analysis based on the DRSA. Decision rules can be defined as logical statement, very easy to understand since they are in the form of 'If… then…' sentences (Słowiński et al, 2009;Cinelli et al, 2015). In Table 7, each rule is represented with the conditions that characterize it, the resulting decision class assignment, and the cases which support it (Cinelli et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Sonication has obviously added to the repertoire of methods employed in synthesis. Ag-NPs, currently obtained by different green routes [92], exhibit a remarkable antibacterial activity, whose mechanism of action has been investigated in detail as well [93]. Thus, Manjamadha and Muthukumar synthesized Ag-NPs in only 10 min using an aqueous extract of Lantana camara L. as bioreductant and capping reagent under ultrasound [94].…”
Section: Ag and Au Npsmentioning
confidence: 99%